Geocomposites on the basis of geomeshes for road and bridge construction - Chizhikov Ilya; Fazilova Zulfiya (E3S Web of Conferences, 2023)
Geosynthetic structures are widely used to prevent destructive anti-erosion, anti-landslide processes in transportation construction. The purpose of this work is to develop a transport structural protective layer with high strength characteristics and the preservation of drainage and anti-erosion properties due to the formation of a flexible volume membrane structure. This structure can also be utilized as a crushed stone layer of a multilayer structure for construction of a transportation section with variable stiffness. The protective layer is formed by adding a polymer binder into the composition of a structural layer, consisting of grain elements. The produced geocomposite is made of layers with different functional properties that ensure its high homogeneous properties in porosity, strength, density, drainage and anti-erosion capacity, self-cleaning tendency, and long service life.